Semi-solid alloy with high wear resistance and preparation method thereof
By electrolyzing the MgZr alloy in the molten salts of magnesium and zirconium, and uniformly dispersing it in the magnesium alloy melt by using bubbles and ultrasonic effects, the problem of low utilization of Zr in the ZK alloy is solved, and the preparation of a semi-solid alloy with high wear resistance is realized.
Patent Information
- Application Number
- CN202510100140.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2045-01-22
AI Technical Summary
In the prior art, the Zr utilization rate of ZK alloys is low, resulting in the need to add 6-7 times Zr to the raw materials to achieve the ideal refinement effect, which increases the cost and is difficult to improve the utilization rate of zirconium.
By placing the porous graphite rod in the molten salt of magnesium and zirconium for electrolytic reaction, an MgZr alloy is formed, and the MgZr alloy is uniformly dispersed in the magnesium alloy melt by using bubbles and ultrasonic effects, thereby improving the utilization rate of Zr.
The Zr utilization rate of ZK-based alloys is achieved, and the cost is reduced, and a semi-solid alloy with high wear resistance is formed by refining the grains.
Smart Images

Figure CN119530894A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of semi-solid alloy materials, and in particular to a semi-solid alloy with high wear resistance and a preparation method thereof. Background Art
[0002] Zirconium is widely used as a refiner in various alloy systems, such as magnesium alloys. The crystal structure of zirconium is the same as that of magnesium alloys, both of which are close-packed hexagonal, and the lattice coefficients are very close, which meets the conditions of being a heterogeneous nucleation core. Zirconium can be used as the crystallization core of α-Mg, thereby producing refined grains, thereby improving the wear resistance of magnesium alloys. However, the solubility of zirconium in magnesium is less than 0.7%. In magnesium alloys, zirconium components mainly exist as a single substance, which is easy to aggregate and cause component segregation and precipitation. Therefore, the amount of zirconium added needs to be strictly controlled. Generally, the problem of zirconium precipitation loss is solved by adding a large amount of zirconium. However, as a rare earth element, its large-scale addition will lead to a significant increase in cost and is difficult to industrialize. Therefore, the preparation of high-wear-resistant alloys by using zirconium as a refiner faces certain challenges. The existing technology generally improves the utilization rate of zirconium by preparing zirconium-magnesium alloys with finer particle sizes. However, the low solubility of zirconium makes zirconium-magnesium alloys with finer particle sizes easy to aggregate during the addition of melts, so this method is difficult to significantly improve the utilization rate (or actual yield) of zirconium. ZK60A magnesium alloy is a Mg-Zn-Zr magnesium alloy that contains a higher content of zirconium. Due to the low utilization rate of zirconium and the loss of zirconium during the preparation process, it is often necessary to add 6-7 times of Zr to the raw materials to achieve the ideal refinement effect.
[0003] Patent CN118497545B previously applied by the applicant discloses a method for preparing a graphene-enhanced magnesium alloy casting, which produces graphene by electrochemically exfoliating a porous graphite rod under ultrasonic action so that the graphene is evenly dispersed in the melt, thereby improving the tensile properties and yield properties of the casting. However, the improvement of the casting performance mainly depends on the strengthening effect of graphene. Although graphene has a certain effect of refining grains, its refining effect is not as good as that of traditional refining agents. When this method is directly used to prepare ZK60A alloy, it is still necessary to add 6-7 times of Zr to the raw material to achieve the ideal refining effect, thereby obtaining a semi-solid alloy with high wear resistance.
[0004] Therefore, it is necessary to provide a semi-solid alloy with high wear resistance and a preparation method thereof. Summary of the invention
[0005] In order to solve the problem of low Zr utilization rate of ZK series alloys, it is necessary to provide a semi-solid alloy with high wear resistance and a preparation method thereof.
[0006] The porous graphite rod is placed in a molten salt containing magnesium and zirconium elements as a cathode for electrolysis reaction, the electrolysis time is 10-30 minutes, and the voltage is 2.7-3V; Obtaining a melt of the alloy in a first container, allowing an inert gas to enter the melt through the porous graphite rod, the flow rate of the inert gas being 5-20 L / min, applying ultrasound to the melt through an ultrasonic probe inserted into the melt, the ultrasonic power being 2-4 kW, and the ultrasonic frequency being 10-30 kHz, and when the solid content of the melt is 10-30%, removing the porous graphite rod and the ultrasonic probe; The melt is transferred to a second container for casting to obtain the semi-solid alloy.
[0007] In this scheme, MgZr alloy is formed on the surface and gaps of porous graphite rods by molten salt electrolysis. At the same time, the precipitated MgZr alloy is inserted into the gaps of the porous graphite rods to promote the exfoliation of the porous graphite rods. The narrow gaps and short electrolysis time of the porous graphite rods limit the growth of the MgZr alloy, so that the MgZr alloy produced by exfoliation has a larger specific surface area. When the treated porous graphite rods are used for the preparation of semi-solid magnesium alloys, under the action of bubbles and ultrasound, the MgZr alloy attached to the surface and gaps of the porous graphite rods is exfoliated with the graphite. The high surface area MgZr produced by exfoliation is not easy to settle under the action of bubbles, and is dissolved in the magnesium alloy melt as the bubbles enter the magnesium alloy melt. Therefore, a higher concentration of Zr is contained around the bubbles, and the magnesium alloy melt forms nuclei around the bubbles. The high concentration of Zr is re-precipitated under the refrigeration provided by the bubbles. The precipitated Zr can serve as a crystallization core of α-Mg to promote the formation of crystal nuclei, thereby obtaining a refined magnesium alloy, and finally forming a semi-solid alloy with high wear resistance.
[0008] Furthermore, the molten salt contains MgCl2, KCl and K2ZrF6.
[0009] Furthermore, the molten salt comprises 20-40 parts of MgCl2, 35-60 parts of KCl, 4-8 parts of KF, and 15-25 parts of K2ZrF6 by weight. By increasing the specific gravity of K2ZrF6, the content of Zr in the MgZr produced by the deposition is increased, and finally the content of Zr in the melt is increased, so as to achieve an ideal refinement effect.
[0010] Further, the voltage is 2.7-2.8 V. The reduction potential of Zr is -0.8 V and -1.2 V, at which Zr can be deposited quickly, while the reduction potential of Mg is -2.67 V. When the voltage is 2.7-2.8 V, the deposition rate of Mg is slow, thereby increasing the Zr content in the deposited MgZr. When the voltage exceeds 2.8 V or even 2.9 V, Mg will be deposited quickly, causing the Zr content in MgZr to decrease and segregation to occur.
[0011] Furthermore, the current density of the electrolysis reaction is (2-5) / (A·cm -2 ). The deposition rate of Mg ions is slow at low charge density, which is beneficial to increase the Zr content in MgZr.
[0012] Furthermore, the pore size of the porous graphite rod is 50-100 nm. In order to facilitate the stripping of MgZr, a porous graphite rod with a larger pore size is required; however, the pore size of the porous graphite rod should not be too large, otherwise the surface area of the porous graphite rod is too small, resulting in excessive reduction in the stripping efficiency of MgZr.
[0013] Furthermore, the mass of Zr in the molten salt is 2-3 times the designed value of Zr in the melt. Considering that the Zr in the molten salt cannot be completely converted into MgZr and deposited on the porous graphite rod, it is necessary to set an excess of Zr in the molten salt. The excess Zr does not cause waste, and MgCl2 and K2ZrF6 can be added accordingly after electrolysis to continue electrolysis.
[0014] Furthermore, the alloy is a ZK alloy. ZK alloys require a relatively high concentration of Zr. Applying this method to the preparation of ZK alloys helps to reduce the cost of ZK alloys and improve the performance of ZK alloys. Furthermore, the ZK alloy is ZK60A. Specifically, the composition of ZK60A includes: by weight, 5-6% zinc, 0.3-0.9% zirconium, 0.10% manganese, and the content of each other impurity is less than 0.05%, and the balance is magnesium.
[0015] Furthermore, the porous graphite rod is made of expanded graphite, which is a worm-like graphite material formed by intercalation, water washing, drying and high-temperature expansion. Expanded graphite has a larger interlayer distance, can accommodate more MgZr during electrolysis, and is more likely to be peeled off under external force.
[0016] A second aspect of the present invention provides a semi-solid alloy with high wear resistance, which is prepared by the above preparation method.
[0017] The above-mentioned semi-solid alloy has improved wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a schematic diagram of the process of the preparation method of embodiment 1 of this scheme.
[0019] Figure 2 This is the metallographic diagram of Example 1.
[0020] Figure 3 This is the metallographic diagram of Comparative Example 1.
[0021] Figure 4 This is the metallographic diagram of Comparative Example 2. DETAILED DESCRIPTION
[0022] For ease of understanding of the application, the application will be described more fully below. The application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the application more thorough and comprehensive.
[0023] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the description of the present application, the meaning of "several" is at least one, such as one, two, etc., unless otherwise clearly and specifically defined.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0025] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0026] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0027] The percentage contents involved in this application, unless otherwise specified, refer to mass percentage for solid-liquid mixing and solid-solid mixing, and refer to volume percentage for liquid-liquid mixing.
[0028] The percentage concentrations mentioned in this application, unless otherwise specified, refer to the final concentration, which refers to the percentage of the added component in the system after the addition of the component.
[0029] The temperature parameters in this application, unless otherwise specified, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range of instrument control.
[0030] The "particles" mentioned in this application, or materials with a defined particle size distribution, are not necessarily spherical in shape, but may be irregular, primary particles or secondary particles. The particle size of irregular particles is the average of their maximum diameter and minimum diameter.
[0031] like Figure 1 As shown, a schematic diagram of the preparation method of an embodiment of the present scheme 1 is shown, and the main steps include: placing a porous graphite rod in a molten salt containing magnesium and zirconium as a cathode for electrolysis, using the porous graphite rod after electrolysis for semi-solid slurrying by gas induction method, applying ultrasonic action to the melt while slurrying, and using the semi-solid slurry for casting.
[0032] Example 1: To prepare a molten salt, 126 g of MgCl2, 189 g of KCl, 25.2 g of KF, and 84 g of K2ZrF6 (the mass of the Zr element is about 27 g) are placed in a crucible and heated to 800°C to form a molten salt. The above materials have been dried before heating.
[0033] A porous graphite rod (cathode) with a diameter of 26 mm, a length of 165 mm and a pore size of 50 nm and a Pt electrode (anode) of the same size were placed in a molten salt and assembled with a DC power supply to form a loop. Electrolysis was performed at a constant voltage of 2.75 V for 10 min. The porous graphite rod was taken out, dried and connected to an argon gas source. The material of the porous graphite rod was expanded graphite.
[0034] Preparation of ZK60A (design value: 5% zinc, 0.9% zirconium, 0.1% manganese and 94% magnesium): weigh 53g zinc and 1050g magnesium, place them in a resistance furnace, stir and heat to 740℃, remove the slag and transfer them to a reaction vessel, cool them to 20℃ above the liquidus to form a melt, place a porous graphite rod in the melt, the bottom of the porous graphite rod is 2mm away from the bottom of the container, place an ultrasonic probe in the container, and set the ultrasonic probe parallel to the porous graphite rod with a spacing of 2cm. Start the argon gas flow, control the gas flow rate to 10L / min, and start ultrasound at the same time, with an ultrasonic power of 4kW and an ultrasonic frequency of 30kHz. When the solid content of the melt is 10% (solid content at the end of cooling), remove the porous graphite rod and the ultrasonic probe, and transfer the melt to the mold for casting. The time from removing the porous graphite rod to the melt completely entering the mold is 20 seconds (melt transfer time).
[0035] Squeeze casting: The semi-solid magnesium alloy melt is die-casted by an extrusion casting machine, with a filling speed of 100 mm / s, a holding pressure of 180 MPa, a holding time of 10 s, and a mold temperature of 300°C to obtain a semi-solid magnesium alloy casting (gear).
[0036] Hardness test method: Test in accordance with the national standard GB / T 7997-2014 "Vickers hardness test method for cemented carbide".
[0037] The experimental conditions of Examples 1-6 and Comparative Examples 1-3 are shown in Table 1. In Comparative Example 1, no electrolysis reaction is performed, but MgZr30 master alloy is directly added to the raw material of the melt at twice the design value; Comparative Example 2 uses a longer electrolysis time; and Comparative Example 3 uses 5 parts of K2ZrF6 in the molten salt raw material.
[0038] Table 1 Experimental conditions of Examples 1-6 and Comparative Examples 1-3.
[0039]
[0040] Table 2 Performance test results of Examples 1-6 and Comparative Examples 1-3.
[0041]
[0042] According to the data in Table 2, the hardness of Examples 1-6 is significantly higher than that of Comparative Examples 1-3, and the corresponding average particle size of Examples 1-6 is lower than that of Comparative Examples 1-3. This is because the present invention forms MgZr alloy on the surface and gap of porous graphite rods by molten salt electrolysis, and the precipitated MgZr alloy is inserted into the gap of porous graphite rods to promote the exfoliation of porous graphite rods, while the narrow gap of porous graphite rods and the short electrolysis time limit the growth of MgZr alloy, so that the MgZr alloy produced by exfoliation has a larger specific surface area. When the treated porous graphite rods are used for semi-solid When preparing magnesium alloy, under the action of bubbles and ultrasound, the MgZr alloy attached to the surface and gap of porous graphite rods is peeled off with graphite. The high surface area MgZr produced by the peeling is not easy to settle under the action of bubbles. As the bubbles enter the magnesium alloy melt, it dissolves in the magnesium alloy melt. Therefore, there is a higher concentration of Zr around the bubbles. The magnesium alloy melt forms nuclei around the bubbles. The high concentration of Zr re-precipitates under the refrigeration provided by the bubbles. The precipitated Zr can serve as the crystallization core of α-Mg to promote the formation of crystal nuclei, thereby obtaining a refined magnesium alloy and finally forming a semi-solid alloy with high wear resistance. Comparative Example 1 adds Zr twice the design value to the melt. However, this amount of Zr cannot achieve the ideal refining effect. Most of the Zr is directly precipitated, forms oxides, or is consumed in other ways, such as Figure 2-Figure 3As shown, the grain size of Comparative Example 1 is significantly larger than that of Example 1, which is difficult to apply; Comparative Example 2 uses a longer electrolysis time. On the one hand, too long an electrolysis time may cause the surface of the graphite rod to peel off, resulting in the Zr content not reaching the expected level. On the other hand, it may cause excessive growth of MgZr particles, which will quickly precipitate during the process of mixing into the melt, and the utilization rate of Example 1 cannot be achieved. Therefore, Figure 4 The grain size is relatively coarse; in Comparative Example 3, too little K2ZrF6 is used, and the Zr content in the MgZr particles is too low. After being dissolved in the melt and further diluted, it is difficult to play a refining role.
[0043] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0044] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a semi-solid alloy with high wear resistance, characterized in that: The following steps are involved: The porous graphite rod is placed in a molten salt containing magnesium and zirconium elements as a cathode for electrolysis reaction, the electrolysis time is 10-30 minutes, and the voltage is 2.7-3V; Obtaining a melt of the alloy in a first container, allowing an inert gas to enter the melt through the porous graphite rod, the flow rate of the inert gas being 5-20 L / min, applying ultrasound to the melt through an ultrasonic probe inserted into the melt, the ultrasonic power being 2-4 kW, and the ultrasonic frequency being 10-30 kHz, and when the solid content of the melt is 10-30%, removing the porous graphite rod and the ultrasonic probe; The melt is transferred to a second container for casting to obtain the semi-solid alloy.
2. The preparation method according to claim 1, characterized in that: The molten salt comprises MgCl2, KCl and K2ZrF6.
3. The preparation method according to claim 1, characterized in that: In parts by mass, the molten salt comprises 20-40 parts of MgCl2, 35-60 parts of KCl, 4-8 parts of KF, and 15-25 parts of K2ZrF6.
4. The preparation method according to claim 1, characterized in that: The voltage is 2.7-2.8V.
5. The preparation method according to claim 1, characterized in that: The current density of the electrolysis reaction is (2-5) / (A·cm -2 ).
6. The preparation method according to claim 1, characterized in that: The pore size of the porous graphite rod is 50-100 nm.
7. The preparation method according to claim 1, characterized in that: The mass of Zr in the molten salt is 2-3 times the designed value of Zr in the melt.
8. The preparation method according to claim 1, characterized in that: The alloy is a ZK alloy.
9. The preparation method according to claim 8, characterized in that: The ZK alloy is ZK60A.
10. A semi-solid alloy with high wear resistance, characterized in that: The semi-solid alloy is prepared using the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Graphene-containing magnesium alloy refiner and preparation method thereof
CN107904428A
MgOHCl aerosol for preparing magnesium alloy semi-solid slurry and using method of MgOHCl aerosol
CN111362287A
Preparation method of graphene reinforced magnesium alloy semi-solid slurry
CN118497545A